Gastroesophageal reflux disease in children including palliative pediatric patients - Yu. Yu. Razuvaeva; V. S. Ledneva; V. V. Leonova; S. A. Leonov; L. V. Ulyanova; O. A. Razuvaev (Лечащий Врач)
Gastroesophageal reflux disease is a retrograde throwing of stomach contents (hydrochloric acid, digestive enzymes and sometimes bile) into the esophagus, which leads to the appearance of symptoms. Gastroesophageal reflux disease occurs more often in palliative patients due to its anatomical features, genetic predisposition in the family, neurological diseases, gastrostasis, prolonged lying down, intolerance to the mixture. For the diagnosis of gastroesophageal reflux disease and esophageal diseases in children, it is possible to use esophagogastroduodenoscopy, daily pH monitoring of the esophagus, gastroesophageal scintigraphy, intraesophageal manometry and X-ray. Most of the techniques are difficult to use routinely in pediatric practice due to invasiveness and radiation exposure, so the use of non-invasive tests is of great importance. One of the non-invasive is ultrasound examination of the stomach, compared with the daily PH-metry of the esophagus, the sensitivity is up to 95%. The aim of the study was to study the clinical and instrumental manifestations of gastroesophageal reflux disease in children. The study was conducted on the basis of the "Zdorovy rebenok" medical center in Voronezh in the period from September to December 2022. During the examination, all children were examined by a gastroenterologist and ultrasound of the stomach with a water-siphon test. During the inspection , the following: clarification of complaints, collection of anamnesis, general examination and special status. Gastroesophageal reflux disease occurs in almost any age group, and most often the onset of the disease occurs at the age of up to 6 years, from which it can be concluded that at the present stage there is a "rejuvenation of the disease". Due to various clinical manifestations, gastroesophageal reflux disease can occur "under the masks of various diseases", which makes it difficult to make a timely diagnosis and delay rational therapy which requires a cautious attitude regarding this disease not only pediatricians and gastroenterologists, but also doctors of other specialties. Ultrasound examination of the stomach is one of the "gentlest" methods of gastroesophageal reflux disease research, which is especially important in childhood, as well as in palliative patients in pediatric practice.